1995
DOI: 10.1002/etc.5620140324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated chlorsulfuron drift on fruit yield and quality of sweet cherries (Prunus avium L.)

Abstract: Field experiments were conducted at the Irrigated Agricultural Research and Extension Center, Prosser, Washington, in 1992 and 1993 to study the effects of simulated chlorsulfuron (2 chloro‐N [[(4 methoxy‐6 methyl 1,3,5‐tnazin 2 yl)amino]‐carbonyl]benzenesulfonamide) drift at different reproductive growth stages of three cherry (Prunus avium L ) cultivars, Rainier, Chinook, and Bing Branches of each cultivar were treated at side‐green, full bloom, postbloom, and pit hardening growth stages with 0, 251 1 × 10 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 12 publications
3
27
0
Order By: Relevance
“…Low application rates of chlorsulfuron influenced the reproduction of four taxonomically diverse species in a manner similar to that shown previously for cherry trees [7,10] and green pea [11]. The magnitude of the reproductive effect caused by the application rates tested depended on the species and the developmental stage.…”
Section: Discussionmentioning
confidence: 60%
“…Low application rates of chlorsulfuron influenced the reproduction of four taxonomically diverse species in a manner similar to that shown previously for cherry trees [7,10] and green pea [11]. The magnitude of the reproductive effect caused by the application rates tested depended on the species and the developmental stage.…”
Section: Discussionmentioning
confidence: 60%
“…Marrs et al (1989) observed that decreases in seed yields of various wild species occurred at greater distances from the origin of spray than decreases in biomass. Other studies have observed similar decreases in seed production (Fletcher et al 1996;Taylor and Oliver 1997;Schmenk and Kells 1998;Riemens et al 2009) and crop yield (Bhatti et al 1995;Al-Khatib et al 2003;Pfleeger et al 2008) to low doses of herbicides simulating drift that are lower than decreases in biomass/vegetative growth as compared to the controls.…”
Section: Introductionmentioning
confidence: 78%
“…Although herbicides have remarkable advantages in protecting crop yields, they can have direct effects on plants pathogens (particularly bacteria and fungi) by either stimulating or inhibiting their growth (Duke et al 2007;Sanyal and Shrestha 2008). In a terrestrial environment, it has been demonstrated that even low concentrations of herbicides can affect the growth and reproduction of non-target plants (Bhatti et al 1995;Boutin et al 2000).…”
Section: Introductionmentioning
confidence: 99%